Bioengineered MSC-derived exosomes in skin wound repair and regeneration - Zhao, Hanxing; Li, Zhengyong; Wang, Yixi; Zhou, Kai; Li, Hairui; Bi, Siwei; Wang, Yudong; Wu, Wenqing; Huang, Yeqian; Peng, Bo; Tang, Jun; Pan, Bo; et al. (Frontiers in Cell and Developmental Biology, 2023)
Refractory skin defects such as pressure ulcers, diabetic ulcers, and vascular ulcers represent a challenge for clinicians and researchers in many aspects. The treatment strategies for wound healing have high cost and limited efficacy. To ease the financial and psychological burden on patients, a more effective therapeutic approach is needed to address the chronic wound. MSC-derived exosomes (MSC-exosomes), the main bioactive extracellular vesicles of the paracrine effect of MSCs, have been proposed as a new potential cell-free approach for wound healing and skin regeneration. The benefits of MSC-exosomes include their ability to promote angiogenesis and cell proliferation, increase collagen production, regulate inflammation, and finally improve tissue regenerative capacity. However, poor targeting and easy removability of MSC-exosomes from the wound are major obstacles to their use in clinical therapy. Thus, the concept of bioengineering technology has been introduced to modify exosomes, enabling higher concentrations and construction of particles of greater stability with specific therapeutic capability. The use of biomaterials to load MSC-exosomes may be a promising strategy to concentrate dose, create the desired therapeutic efficacy, and maintain a sustained release effect. The beneficial role of MSC-exosomes in wound healing is been widely accepted; however, the potential of bioengineering-modified MSC-exosomes remains unclear. In this review, we attempt to summarize the therapeutic applications of modified MSC-exosomes in wound healing and skin regeneration. The challenges and prospects of bioengineered MSC-exosomes are also discussed.